Cooperative Gold Nanoparticle Stabilization by Acetylenic Phosphaalkenes. (23rd July 2015) - Orthaber, Andreas; Löfås, Henrik; Öberg, Elisabet; Grigoriev, Anton; Wallner, Andreas; Jafri, S. Hassan M.; Santoni, Marie‐Pierre; Ahuja, Rajeev; Leifer, Klaus; Ottosson, Henrik; Ott, Sascha
Abstract Acetylenic phosphaalkenes (APAs) are used as a novel type of ligands for the stabilization of gold nanoparticles (AuNP). As demonstrated by a variety of experimental and analytical methods, both structural features of the APA, that is, the PC as well as the CC units are essential for NP stabilization. The presence of intact APAs on the AuNP is demonstrated by surface‐enhanced Raman spectroscopy (SERS), and first principle calculations indicate that bonding occurs most likely at defect sites on the Au surface. AuNP‐bound APAs are in chemical equilibrium with free APAs in solution, leading to a dynamic behavior that can be explored for facile place‐exchange reactions with other types of anchor groups such as thiols or more weakly binding phosphine ligands.